2020
DOI: 10.1016/j.commatsci.2019.109475
|View full text |Cite
|
Sign up to set email alerts
|

First-principle study of the solubility and diffusion of oxygen and boron in γ-TiAl

Abstract: Solubility and diffusion of boron and oxygen in the γ-TiAl intermetallic compound are herein investigated by firstprinciple calculations. On the basis of the space group of the γ phase, the accommodation of the light atoms in the various interstitial positions is studied by density functional theory. Diffusion coefficients are also obtained from ab initio calculations. Barrier energies for the boron and oxygen diffusion among the different stable interstitial sites are computed using the Nudged Elastic Band me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 61 publications
(124 reference statements)
5
21
0
Order By: Relevance
“…As reported in previous works [24][25][26], in the TiAl system, O atoms prefer to occupy 2h sites among many possible interstitial positions, see Fig. 1.…”
Section: Tial-o System a Dft Resultssupporting
confidence: 72%
See 4 more Smart Citations
“…As reported in previous works [24][25][26], in the TiAl system, O atoms prefer to occupy 2h sites among many possible interstitial positions, see Fig. 1.…”
Section: Tial-o System a Dft Resultssupporting
confidence: 72%
“…O atoms are thus located (along the c axis of the tetragonal structure) above an Al atom at an interstitial position, but not at the octahedral position. These earlier studies indicated [24][25][26] that O has a strong affinity with Ti atoms, which explains for instance its high solubility in Ti systems. In these works, it was also shown that other interstitial positions have higher energies than the 2h positions.…”
Section: Tial-o System a Dft Resultsmentioning
confidence: 93%
See 3 more Smart Citations